The Effectiveness of Edutainment toward Pregnancy Care on Knowledge, Attitude, and Action in Pregnant Women - Firdausia, Shalsabilla Tiara; Budihastuti, Uki Retno; Dewi, Yulia Lanti Retno (Journal of Maternal and Child Health, 2021)
Background: Playing or studying in a plea